ANALISIS HUKUM PENGUASAAN TANAH BEKAS HGU OLEH PETANI PENGGARAP (STUDI PENGUASAAN TANAH BEKAS HGU PT.PERKEBUNAN NUSANTARA II OLEH KELOMPOK TANI BERJUANG MURNI DESA MARINDAL 1) - Saddam Hussein; Syafruddin Kalo; Hasim Purba; Edy Ikhsan (Universitas Sumatera Utara, 2018)
ABSTRACT The polemic against access to the distribution of land since the colonial era until now has not found the light of many already the regulations of the Constitution and the MPR TAP until the following rules governing the ownership, designation and management of land. Sometimes the law looks like it is unfair to the peasants, but if it is to be said the law has been arranged in such a way as to ensure legal certainty and legal justice. The problem lies in the state institutions that do not quickly see the problem of land as the case of the former HGU PTPN II area which in fact the land must be linked to the implementation of Landreform in Indonesia.The rights to work on the land have not been clearly written like other rights in the Basic Agrarian Law, but can be interpreted and found in some UUPA Articles and in other laws related to the implementation of land reform, on State lands designated as The object of redistribution is first given